Penerapan PPN Terhadap Tranport Fee di PT Pertamina (Persero) Batam - Maesarah Maesarah (Politeknik Negeri Batam, 2014)
The research for final task was conducted in PT.Pertamina (persero) Batam .The purpose of this research is to know the application of treat the VAT to transport fee from Batam to Tanjungpinang, have been receiving treatment the VAT to transport fee in Tanjungpinang and to know conformity application of tariff used against the provisions of a statute that are currently. The object research covering data calculation transport fee and the reckoning the VAT transport fee from 2 ( two ) agent PT.Pertamina (persero) Batam namely PT.Adri Jaya Sakti which is in Tanjungpinang and PT.Dhiya Kerosene who are in Batam from January 2014 . Data collection method that is used is documentation and interview. The analysis used is descriptive analysis , where 's the writer will disassemble the result of every stage of what is needed in the application of VAT , ranging from studies document until doing the calculations and analyze the accuracy of the fulfillment of the needs of information related to a theme that writer select. From the research is obtained that the application of VAT which is in doing by PT.Pertamina (persero) Batam was in line with areas that have already set , it also applies to the areas of which tax-free